Primary hyperparathyroidism caused by parathyroid-targeted overexpression of cyclin D1 in transgenic mice - Imanishi, Yasuo; Hosokawa, Yoshitaka; Yoshimoto, Katsuhiko; Schipani, Ernestina; Mallya, Sanjay; Papanikolaou, Alexandros; Kifor, Olga; Tokura, Takehiko; Sablosky, Marilyn; Ledgard, Felicia; Gronowicz, Gloria; Wang, Timothy C.; et al. (The Journal of Clinical Investigation, 2001)
The relationship between abnormal cell proliferation and aberrant control of hormonal secretion is a fundamental and poorly understood issue in endocrine cell neoplasia. Transgenic mice with parathyroid-targeted overexpression of the cyclin D1 oncogene, modeling a gene rearrangement found in human tumors, were created to determine whether a primary defect in this cell-cycle regulator can cause an abnormal relationship between serum calcium and parathyroid hormone response, as is typical of human primary hyperparathyroidism. We also sought to develop an animal model of hyperparathyroidism and to examine directly cyclin D1’s role in parathyroid tumorigenesis. Parathyroid hormone gene regulatory region–cyclin D1 (PTH–cyclin D1) mice not only developed abnormal parathyroid cell proliferation, but also developed chronic biochemical hyperparathyroidism with characteristic abnormalities in bone and, notably, a shift in the relationship between serum calcium and PTH. Thus, this animal model of human primary hyperparathyroidism provides direct experimental evidence that overexpression of the cyclin D1 oncogene can drive excessive parathyroid cell proliferation and that this proliferative defect need not occur solely as a downstream consequence of a defect in parathyroid hormone secretory control by serum calcium, as had been hypothesized. Instead, primary deregulation of cell-growth pathways can cause both the hypercellularity and abnormal control of hormonal secretion that are almost inevitably linked together in this common disorder.